Prognostic Impact of Pattern of Mandibular Involvement in Gingivo-Buccal Complex Squamous Cell Carcinomas: Marrow and Mandibular Canal Staging System - Mahajan, Abhishek; Dhone, Navnath; Vaish, Richa; Singhania, Ankita; Malik, Akshat; Prabhash, Kumar; Ahuja, Ankita; Sable, Nilesh; Chaturvedi, Pankaj; Noronha, Vanita; Gosh Laskar, Sarbani; Agarwal, Ujjwal; et al. (Frontiers in Oncology, 2022)
Purpose To study the pattern of mandibular involvement and its impact on oncologic outcomes in patients with GBC-SCC. Propose a staging system based on pattern of bone involvement (MMC: Marrow and mandibular canal staging system) and compare its performance with the 8th AJCC. Methods This retrospective observational study included treatment naïve GBC-SCC patients, who underwent preoperative CT imaging between 01st Jan-2012 and 31st March-2016 at a tertiary care cancer center. Patients with maxillary involvement, masseteric space involvement, and those with follow-up of less than a year were excluded. The chi-square or Fisher’s exact test was used for descriptive analysis. Kaplan Meier estimate and log rank test was performed for survival analysis. Multivariate analysis was done using cox regression analysis after making adjustment for other prognostic factors. P value <0.05 was considered as significant. Based upon the survival analysis with different patterns of bone invasion, a new staging system was proposed ‘MMC’: Marrow and mandibular canal staging system. ‘Akaike information criterion’ (AIC) was used to study the relative fitted model of the various staging (TNM staging – AJCC 8th edition) with respect to survival parameters. Results 1200 patients were screened; 303 patients were included in the study. On radiology review, mandibular bone was involved in 62% of patients. The pattern of bone involvement was: deep cortical bone erosion (DCBE) in 23%, marrow in 34% and marrow with mandibular canal in 43% of patients. Patients with DCBE and no bone involvement (including superficial cortical) had similar survival (DSS, LRRFS) and this was significantly better than those with marrow with or without mandibular canal involvement (p<0.001 for both DSS and LRRFS). Patients with DCBE were staged using the MMC and when compared to AJCC8, MMC system was better for the prediction of survival outcomes AIC values were lower compared to AJCC8. There was significant association (p = 0.013) between type of bone involvement and pattern of recurrence. Conclusions For GBC-SCC, only marrow with or without mandibular canal involvement is associated with poorer survival outcomes. As compared to 8th AJCC, MMC staging system which downstages DCBE correlates better with survival outcomes.